The Effect Of Performance On Social Service Officers, Women Empowerment, Children Protection, Population Control And Family Planning In Holy District On The Distribution Of Social Assistance To The Poor - Luqmatul Karimah; Siti Nurul Kholifah; Qoniatun Ni’mah; Eko Sulistiawan; Ratih Pratiwi (CV Putra Publisher, 2022)
The performance of the Social Service for women's empowerment, child protection, population control and family planning in Kudus Regency in distributing social assistance is highly expected to have qualified personnel, with qualified personnel are expected The assistance will be evenly distributed to the poor or people affected by the epidemic in Kudus Regency. In division This social assistance problem that occurs is related to the data used. Based on these With these problems, this study aims to explain the employees of the Social Service, women's empowerment, child protection, population control and district family planning distribute social assistance to the poor or underprivileged and those affected by Covid-19 outbreaks. The method used in this study is a descriptive method by collecting data through literature study, then conduct a study and then analyze it descriptively qualitative form. The results obtained in this study are the lack of Social Service employees, women's empowerment, child protection, population control and family planning in terms of accountability, because there is a lot of invalid data on the poor so that assistance is not right on target, social services, women's empowerment , child protection, population control and family planning districts are expected to search and provide up-to-date and validated poor community data by the local village government.